2019
DOI: 10.29333/iji.2019.12426a
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed-Method Study of the Epistemological Teacher-beliefs towards Educational Research in Classroom Teaching Practices

Abstract: This study was conducted to identify whether the epistemological teacher-beliefs contributes towards the educational research practice in the classroom. This study involved 500 secondary schools teachers in the East Peninsular Malaysia whereby a mixed-method approach using a standard questionnaire and interview was used. In this study, a questionnaire on Teachers' Perception towards Epistemology (Knowledge) was adapted from Hofer & Pintrich (2002), and to measure Teachers' Perception towards Educational Resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…In other words, female teachers think that educational research is more applicable than male teachers. However, there are also studies reporting that male teachers have more positive attitudes than female teachers in educational research (Erdamar & Akpunar, 2017;İsmail et al, 2019;Kahraman & Köleli, 2017;Yavuz, 2009). However, it should be noted that there are many studies on educational research in which no significant gender difference was found (Baş, 2017;Beycioğlu et al, 2010;Delihasan, 2019;Ekiz, 2006;Gül and Köse, 2017;Kotan, 2019;Sadıç, 2019;Yılmaz, 2020).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, female teachers think that educational research is more applicable than male teachers. However, there are also studies reporting that male teachers have more positive attitudes than female teachers in educational research (Erdamar & Akpunar, 2017;İsmail et al, 2019;Kahraman & Köleli, 2017;Yavuz, 2009). However, it should be noted that there are many studies on educational research in which no significant gender difference was found (Baş, 2017;Beycioğlu et al, 2010;Delihasan, 2019;Ekiz, 2006;Gül and Köse, 2017;Kotan, 2019;Sadıç, 2019;Yılmaz, 2020).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Educational research is very important for teachers to plan and carry out their 524rofessional, skills, competence, and knowledge, educational processes in the light of these data. In this respect, when the literature is examined, there are Many studies examining teachers' attitudes towards educational research, especially in Turkey (Baş, 2017;Beycioğlu et al, 2010;Çepni & Küçük, 2003;De Jong, 2004;Delihasan, 2019;Ekiz, 2006;Erdamar & Akpunar, 2017;Everton et al, 2000;Gül & Pöse, 2017;İlhan, Şekerci, Sözbilir, & Yıldırım, 2014;İsmail et al, 2019;Kahraman & Köleli, 2017;Potan, 2019;Moutafidou, Melliou, & Georgopoulou, 2012 ;Özgenel & Metlilo, 2021;Papasotiriou & Hannan, 2006;Sadiç, 2019;Savlet, 2017;Şahin & Arcagök, 2015;Uçgun & Ünal, 2015;Yavuz, 2009;Yılmaz, 2020). However, there are a limited number of studies that deal with teachers' views on educational research using a mixed method.…”
Section: Introductionmentioning
confidence: 99%
“…The timing of the assessment program is also needed to be considered in ITE. This is important for PSTs to get the experience of assessment into teaching (Hill et al, 2014;Ismail et al, 2019;Izci & Caliskan, 2017;Ogan-Bekiroglu & Suzuk, 2014;Oo et al, 2021). An intervention is needed to ensure that they can perform the assessment demands in the classroom during their professional experience.…”
Section: Use Of a Needs-based Pd Program For Pstsmentioning
confidence: 99%
“…La comprensión de los maestros sobre la investigación educativa y el apoyo de las administraciones escolares para crear una cultura de investigación educativa en la escuela son dos elementos que contribuyen al éxito de la investigación educativa en ellas (Ismail et al, 2019). La existencia de disposiciones organizativas y de un ambiente de confianza y buenas relaciones en las escuelas favorece el aprendizaje, la experimentación y el uso de la investigación .…”
Section: Recomendaciones Y Propuestas De Mejora (Generales)unclassified